Analysis of Students' Mathematical Representation Ability on Cube and Cuboid Topics: A Case Study in A Junior High School - Simanjuntak, Sinitta Marito; Prabawanto, Sufyani (PRISMA, 2025)
This study aims to analyze the ability of mathematical representation on cube and cuboid topic in one of the junior high schools in Bandung. The research design used to achieve the objectives of this study is a case study design that is carried out to investigate students' mathematical representation skills. Data was collected from ten grade IX junior high school students through written tests in the form of descriptions and interviews. Based on the results of the data analysis described above, it can be concluded that the mathematical representation ability of grade IX students at one of the State Junior High Schools in Bandung still has many errors. This is because almost all students have not been able to solve the problems given. Two indicators used in this study, namely visual representation and representation of equations or mathematical expressions, there are still many students who solve mathematical problems that are not completed perfectly and some students are still not thorough and impetuous to find solutions to problems so that students are wrong in providing the final result.